FMRF-amide-like substances in the leech. I. Immunocytochemical localization - Kuhlman, JR (J Neurosci, 1985)
FMRF-amide-like immunoreactivity (FLI) was localized to approximately 50 neurons in each segmental ganglion of the medicinal leech using immunocytochemical techniques. Although most of these neurons were iterated in each segmental ganglion, some were more restricted in their segmental distribution. The head and tail ganglia likewise contained numerous FMRF-amide-like immunoreactive cells. In addition to cell bodies, many nerve processes and varicosities were also immunoreactive throughout the ganglion. All labeling of FLI was blocked by preabsorption of the anti-FMRF-amide antiserum with synthetic FMRF- amide. Using a combination of Lucifer Yellow cellular injection and indirect immunofluorescence techniques, we identified several of the neurons possessing FLI. Identified neurons included excitatory motor neurons (HE, RPE, LPE, AE, and L), the HA modulatory neuron, interneuron cell 204, and cells of unknown function (AP). The processes of HE motor neurons and HA modulatory neurons which innervate the heart tubes were also immunoreactive. These results indicate a role for FMRF- amide-like substances as neurochemical signals in the leech.